Health Workers’ Perceptions of Communication and Interprofessional Collaboration in Digital Primary Healthcare: A Cross-Sectional Study - Delima, Mera; Aljaberi, Musheer A.; Dioso, Redigor III (Qualitative and Quantitative Research Center, 2025)
Interprofessional collaboration is a pivotal strategy for delivering high quality health services during the current global digital transformation. Despite its critical importance, barriers such as professional dominance and frequent miscommunication continue to undermine collaborative efforts in clinical settings. This study analyzed the relationship and association between healthcare workers’ perceptions of effective communication and the actual implementation of interprofessional collaboration within digital health practices. A descriptive analytic cross sectional design was employed using total population sampling of 152 healthcare professionals at a Primary Healthcare Center. Data were gathered through validated questionnaires focusing on digital adaptation and analyzed using Chi-Square tests and Odds Ratio analysis. Findings revealed that 55.3 percent of respondents perceived communication as effective and rated collaboration as good. A significant association was identified (p=0.011) with an Odds Ratio of 7.680. This indicates that healthcare workers with positive communication perceptions are 7.68 times more likely to engage in high quality collaboration. Key challenges identified include hierarchical dominance, instruction miscommunication, and limited team based digital discussion platforms. Effectively, communication serves as the fundamental pillar of coordination in digital health environments. While digital tools such as telemedicine and internal messaging expedite information exchange, success depends on professional communication standards and nursing leadership as care coordinators. Finally, this research contributes a comprehensive and strategic framework emphasizing that nursing leadership as digital mediators is essential for bridging communication gaps, reducing potential clinical errors, and ensuring patient safety in the global Health 5.0 era.